Reduced graphene oxide/palladium nanoparticle bonded to N,N'-bis(2-aminophenyl)-1,2-ethanediamine: a new, highly efficient and recyclable heterogeneous catalyst for direct synthesis of 2-substituted benzimidazoles via acceptorless dehydrogenative coupling of alcohols and aromatic diamine - Kharazmi, Azin; Ghorbani-Vaghei, Ramin; Kharazmi, Arezoo; Azadbakht, Reza; Koolivand, Mostafa; Karakaya, Idris; Karimi-Nami, Rahman (Springer, 2023)
In this paper, the stable synthesis of benzimidazoles catalyzed by reduced graphene oxide/palladium nanoparticle bonded to N,N'-bis(2-aminophenyl)-1,2-ethanediamine (RGO/N-ligand-Pd(0) nanocomposite) through acceptorless dehydrogenative coupling (ADC) of 1,2-phenylenediamine and benzyl alcohol is investigated. The main advantage of this report is the use of RGO/N-ligand-Pd(0) nanocomposite as a new and highly efficient heterogeneous catalyst for the synthesis of a wide range of 2-substituted benzimidazoles using the benign environmental process ADC, because in this process valuable by-products of water and hydrogen gas are produced. The prepared catalyst was identified using various techniques. The results showed that the N-ligand-Pd(0) anchored steadily to the GO nanosheets. The current method has several advantages such as short reaction time, large surface area, and high thermal stability of the catalyst, the ability to reuse the catalyst several times without significant loss of catalytic activity, and the use of benzyl alcohol as a primary material.
Keywords: Acceptorless dehydrogenative coupling (ADC); Benzimidazoles; Nanocomposite; Heterogeneous catalyst; Benzyl alcohol